ANALISIS PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL INTERVENING ( STUDI EMPIRIS PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2012-2014) - RAHMAD DANI (JURNAL ILMIAH KOHESI, 2020)
The purpose of this study is to examine and analyze the effect of ROA, DER, PER, and PBV on Stock Returns either partiallyor simultaneously. To test and analyze the effect of earnings growth on Stock Return. To test and analyze the effect of ROA,DER, PER, PBV on profit growth both partially and simultaneously. To test and analyze the effect of ROA, DER, PER, PBVpartially on Stock Return with Earnings Growth as an intervening variable. The analysis technique used in this study isquantitative data analysis, in practice the research data processing is using SPSS statistical software .Based on the results of ROA and PBV research partially significant effect on Stock Return, while DER, PER partially doesnot significantly influence Stock Return. However, ROA, DER, PER, PBV simultaneously influence the Stock Return. ROAand PER partially have a significant effect on earnings growth, while DER, PBV partially has no significant effect on earningsgrowth. However, ROA, DER, PER, PBV simultaneously influence the profit growth. Partial earnings growth has nosignificant effect on stock returns. Earnings growth is not an intervening variable between the relationship of ROA, DER,PER, and PBV variables with Stock Return.